Financial Inclusion and Consumer Protection in Peru : The Branchless Banking Business - Superintendence of Banks, Insurance and AFPs of Peru; Consultative Group to Assist the Poor (World Bank, Washington, DC, 2015)
As part of its Global Policy Initiative, Consultative Group to Assist the Poor (CGAP) partnered with the Superintendence of Banks, Insurance and AFPs of Peru in late 2008, with the purpose of enhancing the understanding of the issues and trends in consumer relations when financial services are delivered through branchless banking, particularly through agents, which are used in ever increasing scale in Peru. The product was this joint report. Three other countries with relevant experience in branchless banking (Kenya, Brazil and India) participated in a similar exercise at approximately the same time. As in the case of Peru, the exercise gave an opportunity for regulators of each jurisdiction to look at their regulatory and institutional framework for protecting branchless banking users, evaluate their regulatory and supervisory actions, and identify areas for improvements. A forthcoming CGAP focus note complements the effort, by making an overall evaluation of the lessons learned in these countries and drawing on the knowledge from other pioneer countries such as South Africa, Mexico, Colombia and the Philippines. The focus note will point out and address priority areas of concern and possible regulatory and policy options to address them. The first part of the report outlines the financial inclusion efforts currently being undertaken by the Superintendence. The following section summarizes the most important points of the legal and regulatory framework for financial consumer protection, pointing out any specificity of branchless banking. The third part describes the branchless banking business in Peru and describes the issues and problems identified in the relationship between branchless banking clients and providers, and the supervisory and enforcement implications. The last section draws conclusions and makes recommendations for achieving a balance between openness to innovation and protection in a branchless banking environment.